2017
DOI: 10.1159/000481256
|View full text |Cite
|
Sign up to set email alerts
|

Endocan: A Novel Marker of Endothelial Dysfunction in C1-Inhibitor-Deficient Hereditary Angioedema

Abstract: Background: Hereditary angioedema (HAE) related to C1-inhibitor deficiency is a rare autosomal dominant disorder. Vascular cell adhesion molecules (VCAM) are known as endothelial activation markers. Endocan (also called ESM-1) is proposed as an endothelial dysfunction indicator. We aimed to investigate endothelial activation in attack-free periods in HAE patients by measuring their levels of endocan and VCAM-1. Methods: Twenty-six HAE patients (22 female, mean age 40 ± 13 years) and 38 healthy control patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…As the endothelium is inherently related to microvascular permeability and, in consequence, the swelling phenomenon, it represents another area of interest regarding potential biomarkers in HAE. Studies in this field involved vascular endothelial cadherin (transmembrane adhesive protein) [ 72 , 76 ], von Willebrand factor (marker of endothelial damage), soluble E-selectin (cytokine-induced adhesion molecule), endothelin-1 (vasomotor activity regulator) [ 30 , 77 , 78 ], arginine vasopressin , adrenomedullin [ 78 ], atrial natriuretic peptide [ 79 ], as well as endothelial-derived endocan and vascular cell adhesion molecule-1 (markers of endothelial function) [ 80 ]. The subsequently studied modulators of vascular permeability included vascular endothelial growth factors , angiopoietin-1 (which promotes endothelial stabilization) and angiopoietin-2 (which facilitates vascular permeability) [ 81 , 82 ], secreted phospholipases A2 (particularly the 2A group) [ 83 ], and platelet-activating factor acetylhydrolase [ 81 ].…”
Section: Biochemical Biomarkersmentioning
confidence: 99%
“…As the endothelium is inherently related to microvascular permeability and, in consequence, the swelling phenomenon, it represents another area of interest regarding potential biomarkers in HAE. Studies in this field involved vascular endothelial cadherin (transmembrane adhesive protein) [ 72 , 76 ], von Willebrand factor (marker of endothelial damage), soluble E-selectin (cytokine-induced adhesion molecule), endothelin-1 (vasomotor activity regulator) [ 30 , 77 , 78 ], arginine vasopressin , adrenomedullin [ 78 ], atrial natriuretic peptide [ 79 ], as well as endothelial-derived endocan and vascular cell adhesion molecule-1 (markers of endothelial function) [ 80 ]. The subsequently studied modulators of vascular permeability included vascular endothelial growth factors , angiopoietin-1 (which promotes endothelial stabilization) and angiopoietin-2 (which facilitates vascular permeability) [ 81 , 82 ], secreted phospholipases A2 (particularly the 2A group) [ 83 ], and platelet-activating factor acetylhydrolase [ 81 ].…”
Section: Biochemical Biomarkersmentioning
confidence: 99%
“…Endocan is evaluated by peripheral blood serum level, and it is easy to obtain the sample. However, endocan is also not a specific marker and is also increased in atopic dermatitis in serum and lesional skin [ 136 ], psoriasis [ 137 ], and angioedema [ 138 ].…”
Section: Clinical Sign and Biomarker For Drug Eruptionmentioning
confidence: 99%
“…Pathophysiology studies have identified biomarkers (endocan, VE-cadherin) that can help to better clarify the etiology and/or the severity of the disease. [43,44] Genotype-phenotype correlations in C1-INH-HAE disease are currently being extensively investigated. [38,45,46] Speletas et al [45] conducted research in various European countries (Greece, Germany, Romania, and Hungary) and found that abdominal attacks were less common in Hungarians, and that the onset of the C1-INH-HAE type of the disease was delayed in Romanian patients.…”
Section: Serping1 Genementioning
confidence: 99%